Ultrasonic-Assisted Friction Stir Welding on V95AT1 (7075) Aluminum Alloy; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Tarasov S. Yu. Sergei Yulievich; Rubtsov V. E. Valery Evgenjevich; Kolubaev Е. А. Evgeny Aleksandrovich; Ivanov A. N. Aleksey Nikolaevich; Fortuna S. V.; Eliseev A. A. (2015, 2015)
Title screen